Correlation Between Stress Level and Smoking Behavior in Adolescents - Febrian Nur Rahmawati; Agus Sudaryanto (An Idea Health Journal, 2025)
Stress in a person is an unavoidable condition in life. Stress in everyone is generally similar but has an impact. Smoking behavior is defined as the act of burning tobacco products or inhaling vapor from liquids containing nicotine into the lungs. This research was conducted to determine the relationship between stress levels and smoking behavior in adolescents. The type of research carried out in this study used quantitative data, using a random sampling method using a cross sectional study, while for analysis used univariate bivariate analysis and the chi-square statistical test. The sample in this study consisted of 102 students in classes X and XI. The results of the research obtained data in the form of respondents with a stress level of no stress totaling 27 respondents, a moderate stress level totaling 44 respondents, and a mild stress level totaling 31 respondents. Meanwhile, the next distribution showed that 68 respondents were heavy smokers, 19 respondents were light smokers and 15 others were moderate smokers. The results of the chi-square statistical test obtained a p value of 0.045. There is a relationship between stress levels and smoking behavior in teenagers at SMA Batik 1 Surakarta.